Prosodic Prominence in Polar Questions and Exclamatives - Repp, Sophie; Seeliger, Heiko (Frontiers in Communication, 2020)
This study investigates prosodic prominence in string-identical verb-first exclamatives and questions in German. It presents results from three production experiments comparing polar exclamatives/ questions with different finite verbs (auxiliary, lexical verb) and/or subjects (d-pronoun, full phrase) in order to explore the prominence-lending characteristics of different lexical, syntactic and semantic factors, which in other speech acts than exclamatives do not seem to play the same role for prosodic prominence. The results show that clause-initial finite verbs are accented much more often in exclamatives than in questions, indicating that the C-position is an attractor for prosodic prominence in exclamatives. Furthermore, d-pronouns are accented very frequently in exclamatives but virtually never in polar questions. We suggest that the accentuation of the d-pronoun is part of a prosodic constructional default, which is not motivated by syntactic or semantic factors but only by the speech act type. This prosodic construction also comprises a low speaking rate and a reduced sensitivity to information-structural requirements for prosodic non-prominence in exclamatives. The latter assumption is also supported by the finding that given full subjects are accented more often in exclamatives than in questions. With respect to verb type, the findings show that finite auxiliaries are only accented in exclamatives, but that lexical verbs are also accented in questions. Thus, the unergative lexical verbs tested in this study may carry an accent irrespective of clause-initial or clause-final position and independently of speech act.